Ragpa kan pagkaba'go a deconstructive ethnography of the Detritus of modernity in Bikol's coastal villages - Pama, Hermel O. (Department of Anthropology, College of Social Science and Philosophy, University of the Philippines Diliman, 2014)
This deconstructive ethnography devises an indigenous anthropological methodology in tracing archaeological remnants of state-and-foreign-sponsored logging companies at the turn of the 20th century. Field sites are located in the coastal villages of several towns of Camarines Sur, Bikol region, Philippines. Traversing non-traditional methodology and an inter-disciplinary approach, the ethnography demonstrates that tracking the detritus means not only going through geographical terrain, but journeying through the terrain of human transactions, memory and transitions. It foregrounds interrelated domains of materiality, narrative and thought-images in understanding Bikol culture. The valorization of materiality demonstrates deconstruction in ethnographic production. It contributes to Bikol's anthropological and archaeological scholarship through the linking of artifacts and narratives, in documenting the heritage of modernity, capitalism and its local appropriations. The work aims to contribute to new ways of teaching and learning historical archaeology, local history, and tangible and intangible heritage. It augurs a critique of essentialism and contributes to anthropological linguistics by underscoring a way of understanding an economy of emotion behind language.By looking into beliefs and ritual practices, it links religious psychology to the study of collective memory, artifacts and commodities and narrative identity. It delves into the local discourse on power, potency and hegemony, and how these notions are shared across cultures. It inaugurates a discourse in the anthropology of modernity.